The correlation of blood pressure with height and weight in Korean adolescents aged 10-19 years; The Korean National Health and Nutrition Examination Surveys (2009-2011) - Young-Hwan Song (Korean Pediatric Society, 2014)
PurposeHeight-specific blood pressure (BP) is the standard parameter used to diagnose childhood hypertension. However, there has been some argument that weight may be a better variable than height in the reference BP standards. Therefore, before assessing the BP status using the reference BP standards, a basic understanding of the fundamental association of weight and height with BP is required.MethodsIn the present study, we analyzed the correlation of BP with height and weight in Korean adolescents (age, 10-19 years), using data from the Korean National Health and Nutrition Examination Surveys (2009-2011).ResultsSystolic BP (SBP) was more closely correlated with weight than with height in the normal weight (body mass index [BMI], ≤85th percentile) and overweight (BMI, >85th percentile) groups and in the normal waist circumference (WC, ≤90th percentile) and high WC (>90th percentile) groups in both sexes. Diastolic BP (DBP) had a higher correlation with height than with weight in the normal weight and normal WC groups, whereas weight was more closely associated with DBP than height in the overweight and high WC groups in both boys and girls.ConclusionIn Korean adolescents, weight had a greater effect on SBP than height in both the normal weight and overweight groups. DBP was mainly affected by height in the normal weight group, whereas weight was the major determinant of DBP in the overweight group. Therefore, it may be necessary to consider weight in the establishment of reference BP standards.